THE AFFECTING FACTORS ON THE ROLES OF WOMEN IN THE HOUSEHOLD LIVELIHOOD SUSTAINABILITY OF SEAWEED FARMER - Nur Rahmah; Nur Isyana Wianti; Hartina Batoa; Andi Kasirang (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2015)
AbstractThe construction and development of the maritime sector has placed maritme-economic as the basic of economic development in Indonesia is one of the priority of vision and mission that will be realized by The Government of Jokowi. Indonesia, The Maritime Country, holds the potential of huge natural resources, but in fact, it does not provide the better livehood for coastal communities, especially for the household of seaweed farmers in Ranooha Village, South Konawe Regency. The women in Bajo, as part of household systems, act in the income sustainability of households. The purpose of this research is to determine the affecting factor of the roles of women in the household income sustainability of seaweed farmers. This research was conducted at Ranooha Village, Moramo District, South Konawe Regency. The research method is quantitative. The data were analyzed by using Chi-Square analysis tools. The population in this research is the seaweed farmers (households) in Ranooha Village distributing in 4 hamlets. Sample of Hamlets were selected purposively, in terms adapted on the purpose and the need of the research. The sampling technique was perfomed randomly by observing the existing level, which meant that every level of corresponds were represented proportionately. The number of samples in this research were 50 of homogeneous ethnic communities and 50 of heterogeneous ethnic communities. Those were expected to represent the number of the population members. The results showed that the affecting factors of the roles of women in the household livelihood sustainability were women characteristics, living systems, and actions of rasionality.Keywords : Roles, Women, Sustainability, Livelihood, Household, Farmer